Spirituality and humanized care of nursing students from a private university, Peru, 2020 - Larico Calla, Glendy (2020)
Objective: To determine the relationship between spirituality and humanized care provided by nursingstudents from a private university in Peru. Methodology: Quantitative approach, non-experimentaldesign, correlational type and cross section. The sample was obtained by probabilistic sampling,reaching the composition of 117 nursing students. The instruments used were: Caring Efficacy Scalecreated by Coates (1992), adapted to Spanish by Poblete, Valenzuela, & Merino, (2012) with aCronbach’s alpha coefficient of 0.87 and the spirituality questionnaire created by Parsian and Dunning,(2009), adapted and translated into Spanish by Díaz, Muñoz Sánchez and Vargas (2012) with aCronbach alpha coefficient of 0.88. Results: There is a relationship between the variables spiritualityand humanized care with a p-value of 0.004, according to the Spearman correlation statistic. Similarly,a relationship was founded between the dimensions of spirituality (self-awareness, importance ofspiritual beliefs, spiritual practices, and spiritual needs) with humanized care. Regarding the descriptivedata, 84.6% of the students have a high level of spirituality and 54.7% have a high level of humanizedcare. Conclusion: There is a relationship between the study variables.